Conormal symbols of mixed elliptic problems with singular interfaces - G. Harutyunyan; B.-W. Schulze (Հայաստանի ԳԱԱ)
Mixed elliptic problems are characterized by conditions that have a discontinuity on the boundary interface of codimension 1. Earlier additional interface conditions were studied in the case of smooth interface. The present paper studies a structure used in the case of interfaces with conical singularities, namely, corner conormal symbols of the operators. The main focus is on the second order operators and additional interface conditions that are holomorphic in an extra parameter, in particular on the Zaremba problem.
Keywords: Science; Mathematics